Propagation of Game Birds - McAtee, W. L. (Waldo Lee), 1883-1962 (United States. Government Printing Office., 1927)
"Success in the propagation of game birds has been enjoyed in the United States by individuals, by sportsmen's organizations, and by State game departments. There have been failures, of course, but methods that assure success are known. These are treated concisely in this bulletin. Developed methods need only be carried out with energy and intelligence to produce satisfactory results. Raising game birds may be made profitable, since the demand exceeds the supply of adult birds for breeding, of both young and and adults for restocking, and of eggs for distribution to farmers and shooting clubs." -- p. ii. Among the birds discussed are pheasants, quail, partridges, grouse, turkeys, ducks, geese, and swans.